Human Resources Competency Analysis In Facing the Digital Era - Supena, Supena; Sugito, Asep (Pascasarjana STIE Miftahul Huda, 2025)
The Digital Era, which is characterized by technological sophistication and changes in thinking patterns, has influenced various sectors, including the world of work. Human Resources (HR) are required to always follow technological advances and be able to face changes quickly. Human Resources (HR) are a key factor in facing the challenges and opportunities that arise in the current digital era. This research aims to analyze the HR competencies needed to prepare organizations to face the Digital Era. and how organizations can optimize HR potential in improving performance and innovation.